Flexible and versatile pincer-type PGeP and PSnP ligand frameworks - Bestgen, S; Rees, N; Goicoechea, J (American Chemical Society, 2018)
We describe the synthesis and application of two phosphine-functionalized pincer-type N-heterocyclic carbene analogues [(PNNP)E] (E = Ge, Sn) and their reactivity toward main group and precious metal compounds. These flexible tetrelene ligands feature unusual coordination geometries and strong P–E interactions and are expandable to digermylene or distannylene compounds on reaction with ECl2. The compounds were also successfully applied as ligands for the synthesis of Cu, Ag, Au, and Pt complexes. The inherent flexibility of the ligand scaffold enabled different structural arrangements driven by the coordination requirements of the metal centers and intermetallic interactions.